Educational level and cervical cancer screening programs in a Venezuelan urban area. - Núñez-Troconis, José; Velásquez, Jesvy; Mindiola, Raimy; Munroe, David (Investigación Clínica, 2009)
The purpose of this study was to investigate, in a group of Venezuelan women, the knowledge and understanding of the purpose of the Pap smear and the correlation of this knowledge with their educational level. Women were recruited for a cervical cancer screening program and answered a questionnaire concerning what a Pap smear is used for. Three hundred one women were included in the study. Two hundred eighty six women (95%) answered that they knew about Pap smear. Two hundred sixty eight patients (89%) knew that the Pap smear is used for cervical cancer screening. One hundred sixteen women (38.5%) had a low educational level. One hundred and four of them (89.7%) knew that Pap smear is used to screen cervical cancer. Ninety two percent of women who did not complete elementary school had the knowledge of the purpose of vaginal cytology. Two hundred eighty one patients (93%) mentioned that they had at least one Pap smear. One hundred sixty four patients (58.3%) reported to have _ 4 Pap smears in their life time. Two hundred fifty seven women (91.5%) remembered when the first Pap smear was taken. Twenty one patients (7%) had a Pap smear for the first time. The conclusions are: 1) low educational level in an urban area is not a limitation for knowing about and having a cervical cytology test taken; 2) high percentage of Venezuelan women in an urban area know what the Pap smear is used for.